PENILAIAN DAUR HIDUP PRODUKSI GAS BUMI DAN KONDENSAT DI LAPANGAN SOUTH PROCESSING UNIT (SPU) – SWAMP AREA - Doni Agus Sumitro; Arif Kusumawanto; Muslikhin Hidayat (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2020)
ABSTRACT South Processing Unit (SPU) is a gas field that produces condensate and natural gas. The process of producing condensate and natural gas might have an impact to the environment. Life Cycle Assessment (LCA) is a method which measure the environmental impact related to a product of natural gas and condensate processing. This method can be used to evaluate and analyze environmental impacts. This study aims to find out which process units that have a major impact to global warming and human toxicity then provide recommendations for improvements in order to reduce environmental impacts. LCA method and Software SimaPro version developer 9.0 are used during this study. Based on the results, shown the environmental impacts occurred in the process unit for processing gas and condensate product in SPU field. The process units are LP Compressors, Turbo Electric Generator, SCP Flare, SMP Flare, and Sodium Hydroxide Injection. The LP compressors are the biggest contributor for global warming and human toxicity with the impact of 2.855,236 kg CO2 and 8,884 kg 1.4-DB eq. The recommendations to reduce environmental impacts are using biomass as an alternative fuel, adsorption of CO2 with a zeolite adsorbent, and planting of CO2 absorbing plants. Keywords: LCA, South Processing Unit (SPU), SimaPro